The impact of external debt on economic growth in Kenya: An empirical assessment - Maureen Were (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
A group of low-income countries classified as HIPCs have continued to experience difficulties in managing and servicing their huge stocks of external debt. Most of these countries including Kenya are in Sub-Saharan Africa. The relatively high level of Kenya's external indebtedness and rising debt burden has serious implications on the country's development and debt sustainability initiatives. While the economic performance continue to deteriorate, there has been significant net outflow of resources to meet the debt obligations in the 1990s. This paper examines the structure of Kenya's external debt and its implications on economic growth. The findings of the study indicate that Kenya's external debt is mainly official, of which a bigger proportion is from multilateral sources. External debt accumulation has been rising over the years with debt burden indicators increasing steadily in the early 1990s. Using time series data for the period 1970- 95, the empirical results indicated that external debt accumulation has a negative impact on economic growth and private investment. This confirms the existence of a debt overhang problem in Kenya. However, the results also indicated that current debt inflows stimulate private investment. Debt servicing does not appear to affect growth adversely but has some crowding-out effects on private investment. Several policy implications emerge from the study. The simultaneous attainment of sustainable levels of economic growth and external debt appear difficult at the moment and could remain elusive if aggressive measures are not undertaken. In view of the current economic recession and the negative net outflows, the results obtained from this study support the need for Kenya to be considered for comprehensive debt relief measures. There are prospects that availability of these resource flows can stimulate private investments if used productively. A key challenge to the government remains that of ensuring efficiency in delivery of services and increased productivity of public investments. In addition, creating credibility including commitment and political will to reform implementation is required to spur investor confidence for both local and foreign investments.
Keywords: O55; F34; O11; 330; Kenya; debt; growth; Auslandsverschuldung; Wirtschaftswachstum; Kenia